Mortality rates of COPD in deceased COVID-19 patients, a cross-sectional study, Afghanistan, Kabul, 2022- 2023 - Abdulbasit Taib; Abid Sediqi; Saleha Haidari; Razia Miri; Murtaza Jafari (Genius Journals, 2023)
Infections caused by COVID-19 have a high mortality rate in the world and mostly cause weakness in the respiratory system. The existence of several chronic diseases (comorbidities) along with COVID-19 infections causes the development and spread of these infections and increases the mortality rate. COPD is one of the diseases that increase the severity of COVID-19 infections.
Keywords: COVID-19; COPD; Kabul and Mortality rate